2011
DOI: 10.1074/jbc.m110.214460
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a Conserved Tyrosine Residue of Cytochrome b Induces Reactive Oxygen Species Production by Cytochrome bc1

Abstract: Production of reactive oxygen species (ROS) induces oxidative damages, decreases cellular energy conversion efficiencies, and induces metabolic diseases in humans. During respiration, cytochrome bc 1 efficiently oxidizes hydroquinone to quinone, but how it performs this reaction without any leak of electrons to O 2 to yield ROS is not understood. Using the bacterial enzyme, here we show that a conserved Tyr residue of the cytochrome b subunit of cytochrome bc 1 is critical for this process. Substitution of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 48 publications
4
43
0
Order By: Relevance
“…However, that hydrogen bond seems to have only a modest role since the replacement of tyrosine by phenylalanine has little effect on the bc 1 complex function as shown in Table 1, a finding which is in agreement with previous studies using bacterial enzymes (25,27).…”
Section: Figsupporting
confidence: 81%
See 2 more Smart Citations
“…However, that hydrogen bond seems to have only a modest role since the replacement of tyrosine by phenylalanine has little effect on the bc 1 complex function as shown in Table 1, a finding which is in agreement with previous studies using bacterial enzymes (25,27).…”
Section: Figsupporting
confidence: 81%
“…It was previously shown that Y279A, C, and S mutant enzymes exhibited a low SO production, a finding very similar to that observed here (24). Similar observations were reported using Rhodobacter capsulatus Y279 mutants (25). The increase in SO production can be understood in terms of higher semiquinone occupancy at the Q o site, increasing the equilibrium concentration of semiquinone for reaction with oxygen or an increased rate constant for the reaction with oxygen, perhaps by steric means (i.e., an increased probability of collision with oxygen).…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…In human, mutation of this residue causes severe exercise intolerance and "multisystem disorder". 26 In addition, it is known that Tyr268 mutated into Ser in malarial parasite occurred resistance to the antimalarial drug atovaquone. 27 It is also important for catalytic activity of the enzyme in bacteria and yeast.…”
Section: Resultsmentioning
confidence: 99%
“…The positioning of the residue is proposed to be governed by displacement of the PEWY loop (the 'PEWY seesaw') and the docking of the ISP headgroup at the Q o site [30,31]. This proposed 'trapdoor' mechanism is likely to have a role in preventing side-reactions and SO production by minimising semiquinone occupancy at Q o site, a proposal supported by the observation of increased ROS production in mutants equivalent to Y279 in Rhodobacter capsulatus bc 1 complex [32]. It may be postulated that a phenylalanine, having perhaps more degrees of freedom of movement due to the lack of a potentially hydrogen-bonding hydroxyl moiety, is a more efficient trapdoor for the Plasmodium-like Q o site.…”
Section: Fixing the Impaired Q O Sitementioning
confidence: 89%